Signet ring cell carcinoma of the rectal stump in a known ulcerative colitis patient - Asmanaz Nadaf; Ibrahim Hassan Al Haddabi; Ramesh Babu Telugu; Mansour S Al Moundhri (University of São Paulo, 2023)
Colorectal carcinoma (CRC) is the third most commonly diagnosed cancer worldwide and is the second most common cause of cancer-related deaths. However, the Omani population shares the major burden as the most prevalent carcinoma. The disease is comparatively higher in males than females. Patients with pre-existing risk factors, including inflammatory bowel disease, are at increased risk of developing neoplasia. Among the various histopathological subtypes of adenocarcinoma in the rectum, signet ring cell carcinoma is the rarest and accounts for approximately 1% of the cases. Given the aggressive nature of this tumor, advanced presentation, stage, and poor prognosis, regular endoscopic surveillance is essential. Hereby, we report a rare case of signet ring cell carcinoma arising in the rectal stump in an already diagnosed and operated patient of Ulcerative colitis.